The status of government to citizens ICT services in Iraq under the impact of man-made disaster - Abdulrahman, Saifuldeen H.; Kamaruddin, Siti Sakira; Othman, Nafishah (Global Academic Excellence, 2018)
This paper shed the light on the status of the Iraqi government to citizens' ICT services during the latest civil conflict erupted since 2014. These services could fit and serve affected citizens due to the difficulties and risks that hinder their access to the government sites. In the absence of an empirical study to clarify the real status of this kind of services from affected citizens’ perspective during a man-made disaster, this study aims to fill this gap in the literature and handling the lack of knowledge facing the services providers in unstable countries. A survey questionnaire was carried out to 870 internally displaced citizen in six Iraqi provinces to capture their sentiments about the main fundamentals of successful G2CICT services. The results clearly point out the status of these services in regard to availability, benefit, cost, Internet speed, satisfaction, routine, time, and flexibility in such unstable environment.